Development of Virtual Reality Applications - Digital Display for MSME “Tenun Ikat Bandar” Products - Efendi, Fery Sofian; Cinderatama, Toga Aldila; Eliyen, Kunti (Journal of Applied Business and Technology, 2023)
Covid-19 has dramatically impacted the SME sector since April 2020. The government has taken steps to support SMEs as part of the national economic recovery efforts during the pandemic. However, surveys conducted by institutions like BPS, Bappenas, and the World Bank have shown that SMEs need help with loan repayment and meeting expenses for electricity, gas, and employee salaries. SMEs face the challenges of layoffs, limited access to raw materials and capital, declining customers, and production and distribution constraints. Furthermore, changing consumer behavior, business competition, and activity restrictions require proactive measures from SMEs. To address these challenges, a team has proposed a sustainable solution - virtual outlets. Based on virtual reality technology, these outlets allow SMEs to display and sell their products in a digital environment. Visitors can explore every aspect of the virtual outlets, simulating the experience of visiting physical stores without needing in-person visits. This aligns with the new standard of physical/social distancing. Visitors can conveniently support SMEs through online transactions by leveraging virtual outlets, eliminating the need to visit physical stores.